2020
DOI: 10.1097/ijg.0000000000001689
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Ahmed Glaucoma Valve Implantation for Pediatric Glaucoma After Congenital Cataract Surgery

Abstract: Précis: Ahmed valve success for glaucoma following congenital cataract surgery lasts at least 5 years in most eyes, and >10 years in some cases. The procedure is a valuable option for these patients. Purpose: The aim of the study was to report on the results of Ahmed valve implantation in children with glaucoma following congenital cataract surgery. Patients and Methods: Medical records were reviewed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…38 In a recent study looking at Ahmed valve success rates in 41 pediatric GFCS eyes (27 eyes), the probability of surgical success was 95.1%, 89.8%, 83.1%, 72.6% at 12, 24, 60, and 84 months, respectively, with IOP reduction of 51.4% from baseline (P<0.0001). 42 In this study, most eyes (79%) still required medications for pressure control. The most common complication was early hypotony (19.5%).…”
Section: Gfcsmentioning
confidence: 64%
“…38 In a recent study looking at Ahmed valve success rates in 41 pediatric GFCS eyes (27 eyes), the probability of surgical success was 95.1%, 89.8%, 83.1%, 72.6% at 12, 24, 60, and 84 months, respectively, with IOP reduction of 51.4% from baseline (P<0.0001). 42 In this study, most eyes (79%) still required medications for pressure control. The most common complication was early hypotony (19.5%).…”
Section: Gfcsmentioning
confidence: 64%
“…Several studies have demonstrated that success rate decreases with time. [93][94][95][97][98][99] Of all the studies reviewed, only 1 study compared the effect of trabeculectomy with mitomycin-C (Trab+MMC) and Ahmed glaucoma valve with MMC (AGI+MMC), 85 which found that the 2 groups had comparable success and complication rates.…”
Section: Gdd Implantationmentioning
confidence: 99%
“…GDD is applied in the anterior chamber as a shunter to draw the aqueous humor through a tube to a subconjunctival end-plate, including valved (Ahmed glaucoma valve) and nonvalved (Molteno and Baerveldt implants) designs. GDD implantation is currently among the most widely used treatments for GFCS 23,81,85,89–100…”
Section: Treatmentmentioning
confidence: 99%
“…And the most important way to reduce IOP is surgery, with medications being useful as temporizing measures or adjunctive treatment. Meanwhile, surgical options include angle surgery, filtering surgery, glaucoma drainage devices, and cyclodestructive procedures [12][13][14] . However, due to the strong metabolic and repair ability of children, glaucoma drainage device implantation and traditional filtering surgery may increase the risk of scar formation by organized filtration channels.…”
Section: Introductionmentioning
confidence: 99%